The Wild Vanilla of Selangor - Akmal, Raffi; Farah Alia, Nordin; Siti Fatimah, Md Isa; Muhammad Ikhwanuddin, Mat Esa; Micheal Charles, Rajaram; Rusea, Go (Forestry Department of Peninsular Malaysia Headquaters, 2023)
An inventory of the genus Vanilla Plumier ex Mill. in Selangor is updated with the documentation of two additional taxa - a newly described species, Vanilla norashikiniana and the long-lost species, V. montana. To date, the state’s species composition is represented by three taxa including the widespread Vanilla species, V. griffithii. The main aim of this study is to provide important notes on all species recorded in Selangor. The current checklist of genus Vanilla from Selangor was compared to other states within Peninsular Malaysia and the general distribution pattern of each species is proposed.